Bimbingan Online Teknik Penulisan Karya Ilmiah Kualitatif dan Kuantitatif - Masriani Masriani; Muhammad Yusup; Khairul Anwar; Syamsiah Nur; Ferdinan Ferdinan (STAI Auliaurrasyidin Tembilahan, 2021)
This paper described the lecturers' community services in providing an online guidance of qualitative and quantitative research methods at STAI Auliaurrasyidin Tembilahan. This guidance was essential to add insight into scientific writing techniques, especially qualitative and quantitative research. The purpose of this guidance was to make both quantitative and qualitative easier to understand because students will not be away from using these methods. This training was accessible online. This guidance was enthusiastically welcomed by students, both from STAI Auliaurrasyidin Tembilahan and others.